Impact of Municipal Solid Waste Leachate on Surface Water Quality: A Case Study on Kabuturumba Stream. - Rubarema, Paul (Kabale University, 2024)
The purpose of this proposal is to investigate and study the impacts of solid waste leachate on surface water quality. A case study on Kabuturumba stream in Mbarara city. There has been an increasing contamination of surface water sources due to poor methods of waste disposal around Mbarara city and Uganda at large. This study was carried out in different seasons of the year where by samples were collected in dry season and wet season. Different pollution hotspots where also considered in the upstream before joining the stream to clearly understand their potential impacts these points included Coca cola outlet, pearl diary discharge stream and Lubiri stream joining Kabuturumba stream from Kisenyi via Makenke barracks. Different physiochemical and biological parameters were tested in the laboratory. like pH/EC, turbidity, BOD, TDS TSS, heavy metal, bacteriological parameters such the presence of Total coliforms fecal coliforms and E. coli. Different parameters such as COD and BOD levels were found to be extremely high than the environmental standards but later on the hypofiltration or the cleansing capacity of the wetland around the stream helped on reducing them down the stream and almost reached the environmental standards, nutrient levels such as phosphates and Nitrates were also above the recommended values, bacteriological status was extremely higher and later on reduced downstream. The results indicate a level of surface water pollution and toxicities of these pollutants and their threat to human health. The seasonal effects were manifested in that the levels of pollutants increased in wet seasons as compared to dry seasons, this could have been caused by increased surface runoff during wet seasons. The study also indicates that some parameters and pollutants were affected by distance from the dumpsite while others were not.